2017
DOI: 10.1089/hum.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase Gene–Modified Mesenchymal Stem Cells Attenuate Acute Radiation-Induced Lung Injury

Abstract: Radiation-induced lung injury (RILI) is a major clinical complication for radiotherapy in thoracic tumors. An immediate effect of lung irradiation is the generation of reactive oxygen that can produce oxidative damage to DNA, lipids, and proteins resulting in lung cell injury or death. Currently, the medical management of RILI remains supportive. Therefore, there is an urgent need for the development of countermeasures. The present study aimed to evaluate the protective effect of manganese superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…6A). In addition, the overexpression of MnSOD enhanced the protective effects of MSCs on damaged tissue (50,51). What's more, MSCs obtained from umbilical cord showed dramatically elevated MnSOD levels compared with BM MSCs (52).…”
Section: Mnsod In Huc-msc-evs Prevents Hepatocytes From Oxidative Strmentioning
confidence: 95%
“…6A). In addition, the overexpression of MnSOD enhanced the protective effects of MSCs on damaged tissue (50,51). What's more, MSCs obtained from umbilical cord showed dramatically elevated MnSOD levels compared with BM MSCs (52).…”
Section: Mnsod In Huc-msc-evs Prevents Hepatocytes From Oxidative Strmentioning
confidence: 95%
“…Among the several MSC therapy studies conducted in this field include a radiation induced lungs injury experiment, where Liu and colleagues noticed that, although the ordinary MSC decreases apoptosis and infiltration of lymphocyte, and as well increases epithelial cells proliferation and fibrosis inhibition in the later phase, the decorin-modified MSC produces a more enhanced therapeutic effect [118]. Similarly, manganese superoxide dismutase (MnSOD) gene modified MSCs significantly improve radiation induced lung damage, reduce inflammation and protect the cells from apoptosis [119]. In these experiments, the major markers analyzed include inflammatory cytokines levels in plasma, lung histopathology and Treg levels in the peripheral blood and spleen.…”
Section: Lung Injurymentioning
confidence: 99%
“…In these experiments, the major markers analyzed include inflammatory cytokines levels in plasma, lung histopathology and Treg levels in the peripheral blood and spleen. The MnSOD-modified MSCs could differentiate into epithelial-like cells post transplantation in the mice, while the decorin-modified MSCs effectively induce interferon-γ expression, decreased Tregs levels and inhibited collagen type III α1 expression within pulmonary tissues [118,119]. In other respiratory conditions, genetically modified MSC overexpressing angiotensin II type 2 receptor induce higher MSCs migration and accumulation at injured site, accompanied by substantial decrease in pulmonary vascular permeability as well as restored lung histopathology compared to the control group [120].…”
Section: Lung Injurymentioning
confidence: 99%
“…It was reported that MSC‐secreted SOD1 protected lungs from radiation‐induced endothelial cell damage . Similarly, SOD3 or manganese superoxide dismutase‐modified MSCs also have more anti‐inflammatory and antifibrotic effects on RILI, compared with nongene‐modified MSCs . This effect of superoxide dismutase is probably based on their ability to catalyze the dismutation of the superoxide radical into oxygen and hydrogen peroxide, thereby protecting injured cells against ROS generated during RILI .…”
Section: The Potential Of Msc Therapy For Rili Based On the Secretionmentioning
confidence: 99%